Nurse education in Western Australia from 1962-1975: A historical perspective of influences and changes - Piercey, Carol Ann (Curtin University, 2002)
National trends in nurse education have changed from the Nightingale system of on-the-job training to a professional preparation in institutions of higher learning. Western Australia was one of the first States in Australia to commence a professional preparation of nurses at an institution of higher education in 1975. Graduates of the program were presented with their Bachelor of Applied Science from the Western Australian Institute of Technology (now Curtin University of Technology), in March 1979. This thesis seeks to answer the question concerning the genesis of such an event. The focus of the study is primarily to follow the progress of general nurse education in Western Australia and to highlight the accompanying influences that shaped its development. The purpose of this study was to explore, analyse, interpret and describe the history of nurse education in Western Australia from 1962-1975. The study used a pluralistic approach employing a variety of historical methods. The research commenced with broad questions and ideas developed from documents and people. The process of data collection, historical criticism and analysis took place simultaneously. The synthesis was written as a chronological narrative. The material of the study thus 'spoke' for itself by providing answers to questions raised during the investigation. The history of nurse education from 1962 to 1975 revealed visible milestones that represented nurse education reform. Beginning from the antecedents of the study these were the sanctioning of a review of nurse training in 1960 together with the commencement of the Western Australian Nursing Survey and the appointment of the Nurses Registration Board Education Officer. In 1962 the survey was completed.It exposed the deficits of nurse training which led to the development of a new Hospital Based Diploma curriculum and an Associate Diploma in Nursing in 1966. The establishment of the College of Nursing Australia Western Australian Branch in 1966 paved the way to solve the shortage of tutors to implement the Hospital Based Diploma. The Nurses Act in 1970 enhanced the plans for implementing the Hospital Based Diploma and conferred autonomy to the Nurses Registration Board. In 1973 the first independent school of nursing came into being. The Western Australian School of Nursing carried the hopes of a continuation of hospital nurse training. In 1974, however, the entry of students to the Western Australian Institute of Technology School of Nursing saw a turn of events that led to a degree for nurses in 1975 and a decision for the transfer of all nurse education in Western Australia to the Western Australian Institute of Technology. These milestones did not emerge as an accident of history. There were forces that facilitated and impeded the perceptibility of the reform landmarks. These were crucial in the shaping the history of nurse education in Western Australia from 1962-1975.